PENGARUH GAYA HIDUP, MOTIVASI, LITERASI KEUANGAN, DAN PENGELOLAAN KEUANGAN TERHADAP PERILAKU KONSUMTIF BERBELANJA ONLINE MAHASISWA UNIVERSITAS NUSA CENDANA. - Renol Metang (STIE Madani Balikpapan, 2026)
The development of digital technology and the increasing use of the internet have encouraged the increasingly inclusive growth of online shopping activities, especially among university students. This study aims to analyze the influence of lifestyle, motivation, financial literacy, and financial management on students’ consumptive behavior in online shopping at Nusa Cendana University. This study uses a quantitative approach with primary data collected through a questionnaire distributed to 100 respondents selected using the Slovin formula from undergraduate students of the 2021–2024 cohorts. Data analysis was conducted using multiple linear regression with the help of SPSS 27. The results show that partially, lifestyle and motivation have a positive and significant effect on consumptive behavior, while financial management has a negative and significant effect. Meanwhile, financial literacy does not have a significant effect. Simultaneously, all independent variables significantly influence students’ consumptive behavior. This study is expected to increase students’ awareness of the importance of good financial management to control consumptive behavior in online shopping.